1998
DOI: 10.1007/s004260050033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of color on perceptual and conceptual tests of implicit memory

Abstract: Two experiments are reported that explore why recent investigations of implicit memory failed to find any effects of color information on test performance. In the first experiment, participants studied colored pictures as well as words printed in colored ink without any memory instructions. During the test phase, a verbal and a pictorial version of a color-choice task (a conceptual priming test) were compared to two perceptual tests (word-stem completion and picture-fragment identification). Similar and signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 55 publications
2
15
1
1
Order By: Relevance
“…Priming proved to be age invariant: The 6-year-olds showed similar amounts of priming to the 10-year-olds. Moreover, amounts of priming observed in a recent study (Wippich & Mecklenbräuker, 1998) with adult participants (11% to 13% in a verbal and 13% in a pictorial choice task) were not higher than those obtained in the present experiments.…”
Section: Discussioncontrasting
confidence: 84%
“…Priming proved to be age invariant: The 6-year-olds showed similar amounts of priming to the 10-year-olds. Moreover, amounts of priming observed in a recent study (Wippich & Mecklenbräuker, 1998) with adult participants (11% to 13% in a verbal and 13% in a pictorial choice task) were not higher than those obtained in the present experiments.…”
Section: Discussioncontrasting
confidence: 84%
“…The novel and most important discovery of the present study is the finding of substantial color‐specific repetition priming effects. Although several previous investigations (listed in the last section of Table 1) have revealed a priming advantage for objects that were displayed in the same color at study and test, these effects were typically small and not significant, except for one investigation (Wippich & Mecklenbrauker, 1998). In contrast, in the present study we found unambiguous evidence for a color‐specific priming effect.…”
Section: Discussionmentioning
confidence: 78%
“…This can be seen as an involuntary contribution of an episodic memory trace to performances in an implicit memory task. As mentioned, we have already shown that another implicit colour effect, i.e., the preference for old colours in a colouring task (Wippich & Mecklenbra Èuker, 1998) is caused by the same memory traces which are accessed in an explicit memory task . Results from other experiments suggest that object recognition tasks behave similarly, and that also for this task the exemplar specific information is represented within the episodic memory trace and this item-specific memory is independent of memory within generic information caused by implicit effects of the previous study phase.…”
Section: Discussionmentioning
confidence: 93%